Design of broadband phased array antenna at X-band - Wang, Wensong (2018)
Presented is a planar broadband antenna element with a frequency range of 8.33-13.24 GHz for the 15-dB level of return loss. Based on the dielectric notch radiator antenna, this antenna element exhibits the different metallization structure with the uniform slotline at the endfire aperture, and circle arc groove connected to the narrow end of the tapered slotline. The feeding network is one segment of uniform microstrip line on the reverse side of the substrate. The changes can improve the bandwidth, VSWR and gain. It has the size of 1.07λ0 × 1.39λ0 × 0.018λ0, where λ0 is the wavelength at the center frequency in the free space. A 1 × 4 phased array radar antenna is designed with four ports of 50 Ω characteristic impedance. It has the impedance bandwidth (|S11| <; -15dB) of 46.7% from 8.27 to 13.31 GHz and peak gain of 15.5dB at 10GHz. The gain is better than 9.4 dB in the band of interest. The array antenna can form different fan beams by adjusting the input phases of four ports.